2018
DOI: 10.1002/ajp.22909
|View full text |Cite
|
Sign up to set email alerts
|

Social play among black and gold howler monkey (Alouatta caraya) immatures during intergroup encounters

Abstract: We studied intergroup social play (IGSP) among immatures in wild black and gold howler monkeys (Alouatta caraya) in northeastern Argentina. IGSP events are one form of affiliative interaction that can occur during intergroup encounters. The main goal of this study was to analyze IGSP in A. caraya immatures and assess how intrinsic (e.g., age and sex) and extrinsic (e.g., seasonality) factors can influence the development of this type of social behavior. We followed 12 groups between 2008 and 2015 and recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Nonsocial play may serve to improve survival skills and the acquisition of new behavioral patterns (Berghänel et al, 2015 ). In contrast, social play is defined as playful interactions involving two or more individuals that may be beneficial to establishing and maintaining social relationships (Gennuso et al, 2018 ). Studies have shown that play behaviors play an important role in sensory, locomotor, socio‐cognitive, and developmental processes (Fagen, 1981 ; Maestripieri & Ross, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonsocial play may serve to improve survival skills and the acquisition of new behavioral patterns (Berghänel et al, 2015 ). In contrast, social play is defined as playful interactions involving two or more individuals that may be beneficial to establishing and maintaining social relationships (Gennuso et al, 2018 ). Studies have shown that play behaviors play an important role in sensory, locomotor, socio‐cognitive, and developmental processes (Fagen, 1981 ; Maestripieri & Ross, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the motor pattern observed here is very similar to elements observed in typical playful behaviors shown by howlers, like repeated movements, exposing teeth, giving little bites and softening growls, and trying to reach another individual using rapid hand movement. These activities are known to belong to howler's play faces, play invitations, and even play itself (according to the ethograms available in Albuquerque & Codenotti, 2006;Dias & Rangel-Negrín, 2015;de Cunha et al, 2015;Gennuso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, social play is also performed by adults and usually tends to be more expressed when animals are in a low-stress setting (Burghardt, 2014;Montgomery, 2014). Social play has been suggested to represent a means of facilitating tolerance and enhancing social skills and the ability of animals to cope emotionally with unexpected situations (Lewis, 2000;Gennuso et al, 2018), which helps them to bear the risk of conflicts that can escalate into severe fighting (Palagi, 2018). Adult social play can have different functions from those of immature individuals, as play between adults has shorter duration (particularly between males) and is more associated with situations of uncertainty in social relationships, courtship between males and females, or a need to solve or prevent disputes between individuals from the same or different groups (Antonacci et al, 2010;Palagi, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In over 30 primate species, several other mammals and one bird, the existence of reconciliation, third party post‐conflict affiliation and/or consolation behaviour were reported as indicators of high social competence (reviewed in Farooqi & Koyama, 2016). Furthermore, a higher tolerance towards unfamiliar conspecifics (Gennuso et al, 2018), fairness when sharing a resource (Schank et al, 2018), response to other's needs (Dreiss et al, 2017) and cooperation during predator inspection (Hesse et al, 2015), or simply aggregation and sociability (Schausberger et al, 2017) have been associated with social competence in species ranging from invertebrates to mammals. Finally, a lack of social competence has been diagnosed in individuals showing inappropriate aggression, for example after affiliative approach (Kempes et al, 2008) or overly expressed aggression (Toth et al, 2008).…”
Section: Part 2: Positive Feedback Between Social Competence and Soci...mentioning
confidence: 99%